The Project Fair as an Educational Game-based Tool of Students’ Project Activity - Gulyaeva K. V. Kseniya Vasiljevna; Mozgaleva P. I. Polina Igorevna; Zamyatina O. M. Oksana Mikhailovna; Soloviev M. A. Mikhail Aleksandrovich (2015, 2015)
Title screen